Global Challenges, Local Solutions: The Role of Islamic Financial Systems - Ibrahim, Azharsyah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
In this volume, Share Jurnal Ekonomi dan Keuangan Islam (Share Journal of Islamic Economics and Finance) presents a critical examination of the intersections among Islamic finance, economic resilience, and social impact, shedding light on the capacity of Islamic economic principles to offer viable solutions to contemporary global challenges. It provides transformative insights into key areas, including the psychological benefits associated with Islamic social finance, the imperatives of sustainability in corporate governance, and the innovations driving financial inclusion and technology. Utilizing a diverse array of research methodologies—such as bibliometric analysis, structural equation modeling, and comprehensive case studies—the articles contribute robust scholarly insights that focus on promoting psychological well-being, aligning financial practices with sustainability objectives, and leveraging technology to enhance inclusivity. The findings underscore the potential of Islamic economic systems to address both theoretical and practical concerns, emphasizing the adaptability of these principles in fostering equitable socio-economic development and their significance within broader policy and academic discourse aimed at effectively addressing global challenges.